Pemanfaatan Media Gambar Seri Dalam Meningkatkan Keterampilan Membaca Permulaan Siswa Kelas IC SDN Balongsari I / 500 Surabaya - Lilik Eko Nalise (JDP (JURNAL DINAMIKA PENDIDIKAN), 2025)
This study aims to improve the beginning reading skills of first-grade students at SDN Balongsari I / 500 Surabaya through the use of picture series media in Indonesian language learning. Picture series media was chosen because it is believed to help students understand the material more concretely and engagingly, as well as encourage active participation in the learning process. This research is a Classroom Action Research (CAR) conducted in two cycles. Each cycle consists of planning, implementation, observation, and reflection stages. Data were collected through reading skill tests, observations, and reflective discussions between teachers and researchers. The results showed a significant improvement in students' beginning reading skills. The class average score increased from 48.58 in the initial test to 63.57 in Cycle I, and then rose again to 70.00 in Cycle II. Additionally, the percentage of students achieving the learning mastery criteria (score ≥ 60) increased from 32.14% in the initial test to 78.57% in Cycle I, and finally reached 100% in Cycle II. These improvements cover cognitive, affective, and psychomotor aspects, indicating that picture series media is effective in teaching beginning reading. Based on these findings, it can be concluded that the use of picture series media in Indonesian language learning significantly enhances the beginning reading skills of first-grade students, creates a more active and enjoyable learning environment, and increases student participation in the learning process.